A novel score predicts mortality after transjugular intrahepatic portosystemic shunt: MOTS ‐ Modified TIPS Score. (1st April 2022) - Fürschuß, Luisa; Rainer, Florian; Effenberger, Maria; Niederreiter, Markus; Portugaller, Rupert H.; Horvath, Angela; Fickert, Peter; Stadlbauer, Vanessa
Abstract: Background and aims: The high risk for severe shunting‐related post‐interventional complications demands a stringent selection of candidates for transjugular intrahepatic portosystemic shunt (TIPS). We aimed to develop a simple and reliable tool to accurately predict early post‐TIPS mortality. Methods: 144 cases of TIPS implantation were retrospectively analysed. Using univariate and multivariate Cox regression analysis of factors predicting mortality within 90 days after TIPS, a score integrating urea, international normalized ratio (INR) and bilirubin was developed. The Modified TIPS‐Score (MOTS) ranges from 0 to 3 points: INR >1.6, urea >71 mg/dl and bilirubin >2.2 mg/dl account for one point each. Additionally, MOTS was tested in an external validation cohort ( n  = 187) and its performance was compared to existing models. Results: Modified TIPS‐Score achieved a significant prognostic discrimination reflected by 90‐day mortality of 8% in patients with MOTS 0–1 and 60% in patients with MOTS 2–3 ( p  < .001). Predictive performance (area under the curve) of MOTS was accurate ( c  = 0.845 [0.73–0.96], p  < .001), also in patients with renal insufficiency ( c  = 0.830 [0.64–1.00], p  = .02) and in patients with refractory ascites ( c  = 0.949 [0.88–1.00], p  < .001), which are subgroups with particular room for improvement of post‐TIPS mortality prediction. The results were reproducible in the validation cohort. Conclusions: Modified TIPS‐Score is a novel, practicable tool to predict post‐TIPS mortality, that can significantly simplify clinical decision making. Its practical applicability should be further investigated.